Comparison of the new high sensitive cardiac troponin T with myoglobin, h-FABP and cTnT for early identification of myocardial necrosis in the acute coronary syndrome - Kurz, Kerstin; Giannitsis, Evangelos; Becker, Maike; Heß, Georg; Zdunek, Dietmar; Katus, Hugo (Clinical research in cardiology, 2011)
We sought to determine the performance of the new high sensitivity cardiac troponin T assay (TnThs) for early diagnosis of myocardial infarction in patients with suspected acute coronary syndrome (ACS) and compare it with the fourth generation cTnT assay, myoglobin and heart-type fatty acid binding protein (h-FABP).
Published online: 18 September 2010
Gesehen am 11.07.2022